Widening the problem of lead poisoning to a South-American top scavenger: Lead concentrations in feathers of wild Andean condors - Lambertucci, Sergio Agustin (2011)
Lead poisoning is not a new threat for wild birds, but it is now playing an important role in shaping raptor populations. Studies have been focused mainly on Europe, North-America, and Japan, but little is known about the situation in South-America. Lead is a serious threat for wildlife, especially for long-lived species. Nevertheless, no information is available for wild Andean condor (Vultur gryphus) populations. This species, which lives throughout the Andes Mountains, is endangered mainly in the north though it is having problems throughout its distribution. We evaluated lead exposure in the Andean condor by a non destructive method using feathers. We determined lead concentration from 152 feathers, collected in 15 communal roosts distributed throughout almost all condor?s range in Patagonia (ca. 1500 km north-south). We also looked for the origin of this lead through the analysis of lead isotope composition of feathers and ammunition. We present here the first reference data on lead concentration for a raptor population from Argentina. Lead concentrations were generally low, however, some individuals had concentrations several times above the overall mean (up to 21mg/g). Our results suggest that lead might come from a mix of two types of ammunition sources, one used for big game and another for hare hunting. Andean condors are at the top of the food chain, thus all the other medium-to-large sized scavengers and predators from this area can be also exposed to this threat. We highlight the need to change hunting policies in Argentina, and in other Southamerican countries, including the banning of lead ammunitions to protect carnivores consuming hunted animals.